(untitled) - Hirschhoorn, Elisa (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Especies de Tilletia nuevas para la flora argentina (1961)

(untitled)
The autor makes known three new species characteristics of the Argentine flora belonging to Tilletia, which were discovered in materials proceeding from Río Negro, Neuquén and Mendoza. These species are: Tilletia vulpiae P. Mangus, T. bolci (WESTENDORP) DE TONI and T. cerebrina ELLIS et EVERTHART, and she offers analytical illustrations of them.